Engagement among Generation Y (Gen Y) employees at Iskandar Regional Development Authority (IRDA) / Nalyssa Azreen Mohamad Awal - Mohamad Awal, Nalyssa Azreen (Faculty of Business and Management, 2014)
To achieve successfulness, organization should have an engagement between employees. For this study, researcher wants to investigate the engagement among Gen Y employees in IRDA. Employees who are committed and actively engaged in their work will give value to the organization. The purpose of this study is to determine factors that influence engagement among Gen Y employees at IRDA. The research focused on Gen Y employees at IRDA. 75 questionnaires were distributed towards the Gen Y employees. The questionnaires ware used to obtaned data from the respondents. Data was interpreted by using frequencies, reliability, descriptive, correlation and regression analysis.